Selected works of Jonathan Edwards ; v. 1 - Edwards, Jonathan, 1703-1758 (Edinburgh, Scotland Banner of Truth Trust, 1965)
Contents : v. 1 : A compilation of selected works of Jonathan Edwards : "A narrative of surprising conversions" first published in 1736; "Distinguishing marks of a work of the Spirit of God" first published in 1741; "An account of the revival in Northampton in 1740-1742"; and Sermons.
Keywords: Church renewal -- church history -- 18th century